2020
DOI: 10.1519/jsc.0000000000003826
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of Heavy vs. Light Load Ballistic Resistance Training in Older Adults

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Several practical conclusions can be drawn from this study. Both loading conditions and set configurations provoked within-set velocity losses between 10-15 % [15]. While studies in older adults are missing, the extent of velocity losses observed in this study has been shown to be optimal to induce adaptations in high-velocity actions in young adults [58].…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Several practical conclusions can be drawn from this study. Both loading conditions and set configurations provoked within-set velocity losses between 10-15 % [15]. While studies in older adults are missing, the extent of velocity losses observed in this study has been shown to be optimal to induce adaptations in high-velocity actions in young adults [58].…”
Section: Discussionmentioning
confidence: 54%
“…This could be critical in older adults presenting with medical conditions that may aggravate the acute proinflammatory effects of RT, such us low-grade inflammation [51] or a diminished renal function [52]. The lack of significant differences in markers of muscle damage between loads observed in our study may be associated with the similar velocity losses ( ≤ 15 %) [15]. Although light loads have been related to greater metabolic demand and muscle damage than heavy loads [27,28], results obtained in young adults who exercised with different loads ranging from 50 % to 80 % 1RM suggest that significant This document was downloaded for personal use only.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations